Application of the Reciprocal Teaching Model in Class XI Mathematics Learning - Faidah, Alifiya Nur; Darminto, Bambang Priyo; Kurniawan, Heru (Edumaspul: Jurnal Pendidikan, 2023)
This study aims to determine the mathematics learning outcomes of class XI students on the material of the derivative of algebraic functions treated with the reciprocal teaching model and the learning outcomes of students treated with conventional learning models. Applying the reciprocal teaching model in the experimental class is expected to increase student activity in learning. This research method is quantitative research. The design used is a pseudo-experimental design with a non-equivalent control group design. The study population was students of class XI SMA Negeri 1 Buluspesantren. The sampling technique was carried out by cluster random sampling, and one experimental class and one control class were taken. The data collection instruments in this study were pretest and post-test. Prerequisite test analysis using the Lilliefors method for normality test, homogeneity test using the Bartlett method, balance test and homogeneity test using the t-test. The results of data analysis with the t-test show that t_obs>t with t = 1.677 and t_obs = 4.599. The t-test decision is H_0 rejected because t_obs is in the criticism area. From the results of the data analysis, it is concluded that the reciprocal teaching model provides better learning outcomes than the conventional learning model. The reciprocal teaching model in the experimental class can increase student activity in learning.